2012
DOI: 10.7251/qol1201005s
|View full text |Cite
|
Sign up to set email alerts
|

Production of Low Fat Yoghurt Enriched With Different Functional Ingredients

Abstract: Due to a growing demand for functional fermented dairy foods with improved nutritional qualities, the food processing industry has prompted to cut down on ingredients such as fat, sugar and additives, thereby necessitating some important changes in sensory qualities that influence consumer acceptance of fermented dairy products. Addition of functional ingredients such as whey protein concentrate (WPC) and honey may improve overall quality of yoghurt. It is well known ability of WPC to support formation of whey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
1
0
2
Order By: Relevance
“…Higher number of bacteria was observed in Sample 2 compared to the reference (Sample 1) at the end of the storage. Similar results were obtained by Stijeptic [20] who found that the yoghurt enriched in combination of whey protein concentrate and 4% honey had the highest content of lactic acid during the storage period.…”
Section: Resultssupporting
confidence: 88%
“…Higher number of bacteria was observed in Sample 2 compared to the reference (Sample 1) at the end of the storage. Similar results were obtained by Stijeptic [20] who found that the yoghurt enriched in combination of whey protein concentrate and 4% honey had the highest content of lactic acid during the storage period.…”
Section: Resultssupporting
confidence: 88%
“…Penggunaan WPC dengan konsentrasi 0,75; 1,5; dan 2,0% pada yogurt tanpa lemak dapat meningkatkan firmness dan menurunkan sineresis untuk semua perlakuan (Aziznia, 2008). Penambahan 1% WPC dapat meningkatkan viskositas dan WHC pada yogurt rendah lemak (Stijepić et al, 2012).…”
Section: Pendahuluanunclassified
“…The high antioxidant activity of goji berry fruits is due to the high content of polyphenols, flavonoids, carotenoids, etc. [8,11]. This makes them suitable for addition in both fresh and dried state or as extracts in food products and cosmetics.…”
Section: Introductionmentioning
confidence: 99%